IDENTIFICATION AND PREVALENCE OF Edwardsiella tarda BACTERIA INFECTING TILAPIA (Oreochromis niloticus) AT CV SERAMBI IKAN CENTER, LAMBARO - Fauzia Malina; Suri Purnama Febri; Andika Putriningtias; Retno Sari Putri (Universitas Mataram, 2026)
Edwardsiella tarda is a gram-negative pathogen that can cause serious disease in fish, including mass mortality. Tilapia fish infected with E. tarda bacteria show clinical symptoms such as sore skin, swelling and decreased appetite. Bacterial identification was carried out at the SKIPM Laboratory, Aceh Besar, to confirm the presence of E. tarda using biochemical tests. The target organs taken for the isolation process are the liver, kidneys and spleen. This research uses a descriptive survey method with sampling using a purposive sampling technique. The results of the research show the morphological characteristics of the bacterial colony which, when viewed from above, is round, flat, intact and whitish in color. The observation table data from the identification results showed that two fish samples with sample codes N5 and N7 were infected with Edwardsiella tarda bacteria in the same target organ, namely the liver. Bacteriological examination through biochemical tests, Edwardsiella tarda bacteria showed negative results in the 3% KOH test, positive in the indole test, and negative in the oxidase test. The prevalence rate of bacterial attacks obtained from the 10 fish samples used was 20% of the total samples.